The geography of tourism and recreation : - Hall, Colin Michael (Routledge, 2006)
The fully updated third edition of this highly successful and acclaimed text continues to offer a comprehensive synthesis of the key issues associated with the area of tourism, leisure and recreation. It provides a cohesive overview of the landmark studies that exist within tourism, leisure and recreation at a time of rapid growth in the subject area. The book offers the reader a series of chapters which not only explain how important tourism and leisure are in modern society, but also outline the key contributions made by geographers in the global growth of tourism and leisure research.".